Regulation Mechanism of Spatial Capacity of Tourist Resources in Scenic Spots Based on Internet of Things Technology - Xiaona Xie; Wenliang Zhang (Complexity)
At present, it is urgent to solve the problem of scenic area tourism environmental capacity. This paper analyzes the causes of congestion and overload in scenic spots and then points out that the methods to solve the problem are capacity restriction and flow control. This paper first calculates the spatial capacity of various tourism resources in a scenic spot by using mathematical model and then studies the intelligent spatial management model of tourist flow in the scenic spot based on the Internet of Things technology. Based on the Internet of Things technology, the spatial capacity control platform of tourist resources in scenic spots built in this paper can realize the structure analysis of peak forest of tourist flow in scenic spots and the fractal and fractal dimension analysis of tourist flow and determine the spatial and temporal threshold of tourist flow control in tourist destinations. Through capacity restriction and flow regulation, tourists can be scientifically channelled and distributed, which can greatly reduce congestion and overload, enhance tourist experience, and improve tourist satisfaction, so as to promote the sustainable development of the scenic spot.